2021
DOI: 10.1101/2021.04.22.21255908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning from the resilience of hospitals and their staff to the COVID-19 pandemic: a scoping review

Abstract: BackgroundThe COVID-19 pandemic has brought huge strain on hospitals worldwide. It is crucial that we gain a deeper understanding of hospital resilience in this unprecedented moment. This paper aims to report the key strategies and recommendations in terms of hospitals and professionals’ resilience to the COVID-19 pandemic, as well as the quality and limitations of research in this field at present.MethodsWe conducted a scoping review of evidence on the resilience of hospitals and their staff during the COVID-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
1
2
0
3
Order By: Relevance
“…Frontliners aptly noted the hospital's role in fulfilling their primary functions in service delivery but also additional functions in health promotion, community engagement, and risk mitigation. This is consistent with global literature on hospitals during health emergencies where the primary objective of resilient hospitals is to “maintain their function, which occurs when they provide quality (safe, effective, patient-centered, timely, efficient, equitable) and continuous critical and essential services, amidst the crises, while leaving no one behind” ( 2 , 21 24 ). Whereas historically public health functions have been associated with primary care; recent evidence on building resilient health systems to achieve UHC and health security highlights the contributions of all health systems actors (including hospitals) in fulfilling EPHF ( 13 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Frontliners aptly noted the hospital's role in fulfilling their primary functions in service delivery but also additional functions in health promotion, community engagement, and risk mitigation. This is consistent with global literature on hospitals during health emergencies where the primary objective of resilient hospitals is to “maintain their function, which occurs when they provide quality (safe, effective, patient-centered, timely, efficient, equitable) and continuous critical and essential services, amidst the crises, while leaving no one behind” ( 2 , 21 24 ). Whereas historically public health functions have been associated with primary care; recent evidence on building resilient health systems to achieve UHC and health security highlights the contributions of all health systems actors (including hospitals) in fulfilling EPHF ( 13 ).…”
Section: Discussionsupporting
confidence: 83%
“…Fourthly, regarding strengthening hospital resilience throughout the recovery phase; hospital managers highlighted the components of hospital resilience namely resilient staff, sustainable finance, and adaptive leadership and management. Firstly, qualitative findings from this study echoed global literature confirming that the ability to surge staff and redistribute health workers according to hospital needs was critical to the hospital's response, recovery, and ultimately resilience ( 6 , 14 , 24 , 27 , 28 , 41 , 42 ). Given the prolonged response and recovery phases of COVID-19 over the last 3 years, scaling up mental health services and psychosocial support as well as providing training on stress, time, and crisis- management is essential to recovery ( 2 , 15 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, strategic HR planning along with appropriate staff financing for different surge and outbreak scenarios, providing holistic incentive packages (including health insurance), developing better working environments, expanding scopes of work, exploring task-shifting especially in health promotion and risk communication were all suggested solutions to reduce brain wastage and optimise human resource management for outbreaks 2 20–23. Our study also revealed the need to prioritise hospital staff mental health, emergency and stress management, and equip hospital managers on motivating burn-out staff.…”
Section: Human Resourcesmentioning
confidence: 79%
“…B. durch die Absage elektiver Eingriffe oder Rehabilitationen, posteriorisiert [4][5][6][7]. Ebenso mussten vielerorts zur Bewältigung personeller Engpässe nicht mehr aktiv tätige Gesundheitsfachkräfte (u. a. ehemaliges ärztliches und pflegerisches Personal), ärztliches Personal in Ausbildung und Studierende rekrutiert werden, um bei der Behandlung von COVID- 19 Erkrankten mitzuwirken [8,9]. Darüber hinaus war es notwendig, die Belegschaft auf individueller Basis zu unterstützen, sodass sie über einen längeren Zeitraum ihre volle Leistungsfähigkeit entfalten konnten [10].…”
Section: Zielsetzungunclassified
“…Dabei werden insbesondere Aspekte der Personal-und Materialressourcen als auch die strukturelle Beschaffenheit der Organisation selbst als befähigende Komponenten oder Prozesse der organisationalen Resilienz gesehen. Im Kontext der COVID-19 Krise wurde die organisationale Resilienz von Gesundheitseinrichtungen v. a. in der Sicherstellung der Gesundheitsversorgung unter Beibehaltung medizinischer Qualitätsstandards sowie der Aufrechterhaltung der physischen und mentalen Gesundheit der Gesundheitsfachkräfte gesehen [9,20]. In Zusammenschau bedeutet dies, dass sowohl die systemische Resilienz als auch die Struktur, Reaktionsund Anpassungsfähigkeit der einzelnen Akteure und Leistungsan-1 https://www.bosch-health-campus.de/de/wer-wir-sind (Letzter Zugriff am 06.08.2023) bieter einen bedeutenden Faktor in der Begegnung dieser und zukünftiger Krisensituationen darstellen wird [21].…”
Section: Zielsetzungunclassified